2022
DOI: 10.1177/00221678221075910
|View full text |Cite
|
Sign up to set email alerts
|

Meaning-Making Predicts Forgiveness as an Indicator of Posttraumatic Growth with a Stronger Effect for Natural Disasters

Abstract: Trauma is a growing public health concern as global crises increase. Trauma can result in significant adverse psychological outcomes such as posttraumatic stress disorder (PTSD). Past research indicates that forgiveness may buffer the adverse psychological effects of trauma. We hypothesized that restoring individual and collective sense of meaning promotes forgiveness toward self and others and enables posttraumatic growth (PTG). Established PTG models posit that meaning can be found in surviving a traumatic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Similar to how meaning-making can lead to better adjustment for people after natural disasters (Cameron et al , 2022; Park, 2016), terrorist attacks (Park et al , 2012) and wars (Matos et al , 2021), being able to make sense of life during COVID-19 provides some relief of the distress caused by the pandemic. Consistent with the literature on the benefits of meaning-making, recent evidence shows that meaning-making can not only serve as a protective factor but also function as an effective coping mechanism during COVID-19 across nations, ethnicities and ages.…”
Section: Meaning In Lifementioning
confidence: 99%
“…Similar to how meaning-making can lead to better adjustment for people after natural disasters (Cameron et al , 2022; Park, 2016), terrorist attacks (Park et al , 2012) and wars (Matos et al , 2021), being able to make sense of life during COVID-19 provides some relief of the distress caused by the pandemic. Consistent with the literature on the benefits of meaning-making, recent evidence shows that meaning-making can not only serve as a protective factor but also function as an effective coping mechanism during COVID-19 across nations, ethnicities and ages.…”
Section: Meaning In Lifementioning
confidence: 99%
“…In summary, covariance networks found were centered on six key regions, and representative images are shown in (5) of seed regions including the left STG, right IPL, and left ITG with the bilateral PCC (Figure 3E); (6) of seed regions including the left insula and precentral gyrus with the bilateral precuneus (Figure 3F). All these findings survived the p-RFT < 0.05 correction.…”
Section: Interregional Network Substrates: Structural Covariance Netw...mentioning
confidence: 99%
“…Prior findings have suggested that children and adolescents are more vulnerable to developing PTSD after catastrophic events than are adults ( 4 , 5 ). As a collective trauma caused by natural disasters, earthquakes have caused more extensive trauma to the public representing the negative impact on social processes at the collective level compared to individual crisis events ( 6 ). The devastating Wenchuan 8.0-magnitude earthquake resulted in heavy casualties and seriously affected approximately 46 million people, of whom a considerable number were suffering from PTSD ( 7 ).…”
Section: Introductionmentioning
confidence: 99%